Progression of Radiation Protection in Radiology & Imaging - Arfat, Mohd.; Nisha, T K; Taiba; Jha, Samita; Yadav, Jyoti; Zahiruddin, Md. (British Journal of Healthcare and Medical Research, 2024)
Radiation protection stands as a critical imperative in our modern technological landscape, where various industries, such as medicine, nuclear energy, and manufacturing, rely on the controlled use of ionizing and non-ionizing radiation. This paper underscores the paramount significance of radiation protection and underscores the imperative for perpetual advancements in this domain. As the utilization of radiation becomes more prevalent in diverse sectors, the potential risks associated with exposure necessitate constant vigilance and refinement of protective measures. The abstract offers a concise introduction to the multifaceted dimensions of radiation protection, emphasizing its pivotal role in safeguarding human health, the environment, and ensuring the sustainable development of technologies reliant on radiation. The ensuing exploration of current practices, recent technological innovations, and future trends collectively contribute to a comprehensive understanding of the evolving landscape of radiation protection.